Sustainable Community Assistance Model as an Effort to Improve the Welfare of the Mangliawan Community - Susilawati, Samsul; Supriyatno, Triyo; Nur, Muhamad Amin; Avista, Candra; Rahmi, Sri Nur (World Psychology, 2025)
The issue of community welfare remains a persistent challenge in many developing regions, including the village of Mangliawan. Despite having abundant local potential and human resources, the community continues to face economic instability, limited access to education, and underutilized social capital. This activity aims to empower the community to create new independent entrepreneurs, encouraging the empowerment of family entrepreneurs to increase family income and job opportunities through network expansion. This research was carried out in Mangliawan Village, Pakis District, Malang Regency, which is a center to produce snacks, such as tempeh chips and snacks, and the processing of used frying oil waste into aromatherapy candles. The aim of this activity is to provide guidance and assistance to the community in making candles. environmentally friendly aroma therapy and its marketing, thus becoming a new business expansion to increase family income. This service activity uses a Participatory Rural Appraisal approach which gives partners the opportunity to actively participate in activities from problem identification to the end of the activity. The targets of this community service activity are housewives living in Mangliawan Village, Pakis District, Malang Regency who have low incomes. There are four training activities to empower housewives, namely vocational training on packaging aromatherapy candles, tempeh chips, product packaging training, branding, and digital marketing strategies. The impact of this activity is that it contributes to improving the family's economy, the community can create and manage an environmentally friendly aromatherapy candle business and is very motivated to use and market it because they are aware that it can help efforts to improve the quality of the environment.